2009
DOI: 10.1016/j.jpain.2008.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Phosphorylation of Extracellular Signal-Regulated Kinase in Trigeminal Nociceptive Neurons Following Propofol Administration in Rats

Abstract: Although propofol (PRO) is widely used in clinic as a hypnotic agent, the underlying mechanisms of its action on pain pathways is still unknown. Sprague-Dawley rats were assigned to receive PRO or pentobarbital (PEN) and were divided into two groups as LIGHT and DEEP hypnotic levels based on the EEG analysis. Rats in each hypnotic level received capsaicin injection into the face and phosphorylated extracellular regulated-kinase (pERK) immunohistochemistry were performed in subnucleus caudalis (Vc) and upper ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…However, several studies reported that capsaicin-induced apoptosis and pain responses in neurons are mediated by ERK activation (Gao & Ji, 2009;Shirakawa et al, 2008;Shoda et al, 2009). Data thus suggest that capsaicin may have cell-type-specific properties in proliferating cells and postmitotic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies reported that capsaicin-induced apoptosis and pain responses in neurons are mediated by ERK activation (Gao & Ji, 2009;Shirakawa et al, 2008;Shoda et al, 2009). Data thus suggest that capsaicin may have cell-type-specific properties in proliferating cells and postmitotic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…While the caudal peak of neuronal activity varies rostrocaudally and mediolaterally in the Vc according to somatotopy, the rostral peak is consistently located at the obex or the trigeminal transition zone level (Strassman and Vos, 1993). Further, anesthetic alone induces Fos protein expression and increased phosphorylation of the extracellular signal-regulated kinase in the Vi/Vc transition zone (Imbe et al ., 1999; Shoda et al ., 2009). These findings suggest that neuronal activation in the ventral Vi/Vc transition zone lacks somatotopy, although there are selective primary afferent inputs to the Vi/Vc transition zone (Klineberg, 1971; Shigenaga et al ., 1988; Pozo and Cervero 1993; Zhou et al ., 1999; Hirata et al ., 1999; Imbe et al ., 1999; Wang et al ., 2006).…”
Section: Functional Significance Of Vi/vc In Trigeminal Pain Procmentioning
confidence: 99%
“…Extracellular signal-regulated protein kinase (ERK) is a member of mitogen-activated protein kinase family that can be activated by calcium influx within 10 min after noxious stimulation [11] . Phosphorylated ERK-immunoreactive (pERK-IR) cells are known to be distributed in Vc with somatotopic organization, and the number of pERK-IR cells increased in an intensity-dependent manner in the Vc [12] .…”
Section: Introductionmentioning
confidence: 99%